2014
DOI: 10.1080/14786419.2014.968155
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition effect of phenyl compounds from theOryza sativaroots on melanin production in murine B16-F10 melanoma cells

Abstract: Five phenyl compounds, vanillin (1), methyl trans-ferulate (2), trans-p-coumaric acid methyl ester (3), N-benzoyltryptamine (4), and N-(trans-cinnamoyl)tryptamine (5), were isolated from the roots of Oryza sativa L. and identified on the basis of spectroscopic data. Compounds 3 and 5 showed strong inhibition effect on melanin production in murine B16-F10 melanoma cells and tyrosinase activity. Also, the quantitative analysis of the compounds was carried out using LC/MS/MS experiment. Compounds 3 and 5 could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…O. sativa has bioactive compounds, including many phenolic compounds as an antioxidant 17 . Five phenyl compounds isolated from the roots of O. sativa L. are vanillin, methyl trans-ferulate, trans-p-coumaric acid methyl ester, N-benzoyltryptamine, and N-(trans-cinnamoyl) tryptamine 40 . Phenols can be divided into two subgroups according to their structure, p-hydroxybenzoic acid derivatives such as gallic, protocatechuic and syringic acids, and hydroxycinnamic derivatives such as caffeic, ferulic, p-coumaric and chlorogenic acids 19 .…”
Section: Discussionmentioning
confidence: 99%
“…O. sativa has bioactive compounds, including many phenolic compounds as an antioxidant 17 . Five phenyl compounds isolated from the roots of O. sativa L. are vanillin, methyl trans-ferulate, trans-p-coumaric acid methyl ester, N-benzoyltryptamine, and N-(trans-cinnamoyl) tryptamine 40 . Phenols can be divided into two subgroups according to their structure, p-hydroxybenzoic acid derivatives such as gallic, protocatechuic and syringic acids, and hydroxycinnamic derivatives such as caffeic, ferulic, p-coumaric and chlorogenic acids 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The phenolic acid moieties in phenylamide phytoalexins suggest that they likely act as allelochemicals in rice. In addition to UV and pathogen induced accumulation of phenylamide phytoalexins in rice leaves, CinTrp and BenTrp were isolated from rice roots without external stimulus [ 57 ]. A recent study also demonstrated that the phenylamide CinTyr isolated from rice acts as an allelochemical that inhibited root and hypocotyl growth of cress, barnyard grass, and red sprangletop [ 58 ].…”
Section: Phenolic Phytoalexins In Ricementioning
confidence: 99%
“…[2] Extracts of O. sativa have shown pharmacological effects including antiviral, [3] antitumor, [4] antifungal, [5] antimicrobial, [6] and antimelanogenic effects. [7] Previous phytochemical analysis experiments of O. sativa have reported the presence of bioactive compounds including diterpe-noids, [3,5,8] gibberellins, [3,6] phytosterols, [9] and phenolic compounds. [7] As part of our ongoing efforts to identify significant bioactive compounds in Korean medicinal plants, [10 -17] we have investigated bioactive compounds from the roots of O. sativa and were recently able to identify two new lignans, oryzativols A and B, that reciprocally regulate adipocyte and osteoblast differentiation from the ethanolic extract of O. sativa root.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Previous phytochemical analysis experiments of O. sativa have reported the presence of bioactive compounds including diterpe-noids, [3,5,8] gibberellins, [3,6] phytosterols, [9] and phenolic compounds. [7] As part of our ongoing efforts to identify significant bioactive compounds in Korean medicinal plants, [10 -17] we have investigated bioactive compounds from the roots of O. sativa and were recently able to identify two new lignans, oryzativols A and B, that reciprocally regulate adipocyte and osteoblast differentiation from the ethanolic extract of O. sativa root. [18] Inspired by the discovery of bioactive lignans, we continued to investigate the EtOH extract using a comparative LC/ MS-based analysis approach.…”
Section: Introductionmentioning
confidence: 99%